Social Capital and Quality of Life among Urban and Rural Older Adults. Quantitative Findings from the Irish Longitudinal Study on Ageing - Ward, Mark; Mc Garrigle, Christine; Kenny, Rose (My University, 2021)
While the association between health and quality of life (QoL) is well established, our understanding of the effect of inter-relationships and the wider social context is less well understood. Our aim was to examine the association between social capital, area-level deprivation, quality of relationships, and the control/autonomy domain of QoL. Data was from The Irish Longitudinal Study on Ageing (TILDA), a prospective nationally representative study of community-dwelling older adults in the Republic of Ireland. QoL was measured using CASP-19. Mixed effects linear regression models were estimated, stratified by urban rural location. QoL increased until around 68 years before decreasing into oldest age. Social cohesion was associated with the QoL of urban participants while social decay was important to the QoL of both urban and rural participants. Functional limitations, depressive symptoms and loneliness were also associated with poorer QoL. Social capital and the socio-economic environment influence QoL, independent of other factors. We show that the relationship between the social environment and QoL differs between rural and urban populations. While social decay was important in both settings, social cohesion was related to QoL among urban dwellers only and higher levels of area level deprivation was associated with lower QoL among rural residents.
PUBLISHED
Keywords: Social environment; Ageing; Older adults; Quality of life; CASP-19; Social capital; Ireland; Ageing; Inclusive Society